Hi everyone, i am totally stumped with this section of my coarse work, Maths is not my friend, and my father, who is a maths 1,2 and calculus teacher can't for the life of him work these two out, thus i have resorted to my last ... resort ... ANY help would be greatly appreciated in working out these recursive relations.

a)

an = a(n/2) + n, for n >=2, with a1 = 0

substitute n = 2^k, solve with iteration,

thus,

a2^k = a2^(k-1) + 2^k

= a2^(k-2) + 2^(k-1) + 2^k

=a2^(k-3) + 2^(k-2) + 2^(k-1) + 2^k

Im stumpted here on, not a clue really as all the text book examples and lecturers examples do not follow these patterns.

Also

b)

an = a(n/2) + n^2, for n >=2, with a1 = 0

Not a clue ...

Due tomorrow so im cutting it close, otherwise its a slap on submit job. (no there were 30 other questions i've done this isn't a last minute job, last 2 questions.)

Thank you!!

Mathzea